Mycotic aneurysm due to Salmonella species: clinical experiences and review of the literature - Yiqun Guo; Yu Bai; Chunxia Yang; Peng Wang; Li Gu (Brazilian Journal of Medical and Biological Research, 2018)
The mortality of patients with mycotic aneurysms is high, especially in East Asia, and infection by Salmonella species is the most common. Our study aimed to improve prognosis of adult mycotic aneurysms with early diagnosis and accurate treatment. Four adult patients with mycotic aneurysm caused by Salmonella were included and analyzed by single-center retrospective analysis. Cases reported in the literature during the past 10 years were also summarized. The average age of the 4 male patients was 61.25 years, while that of the 53 cases reported in the literature was 65.13 years. Hypertension, diabetes, and atherosclerosis were common complications. Most patients presented fever and experienced pain at the corresponding position of the aneurysm. Laboratory examination found an increased number of white blood cells accompanied by an increase in inflammatory markers. Most aneurysms were found in the abdominal aorta, while the rupture of an aneurysm was the most common complication. The mortality rates were 21.43 and 7.14% after open surgery or endovascular aneurysm repair (EVAR) intervention, respectively. The recurrence rates of infection were 0 and 17.85% for both treatments, respectively. The mortality rate of mycotic aneurysm caused by Salmonella infection was high in middle-aged males with hypertension, diabetes, and atherosclerosis. The possibility of a Salmonella-infected aneurysm should be considered in these high-risk groups presenting chills, fever, chest, and back pain. Open surgery was superior to EVAR treatment in the clearance of infected foci and the reduction of postoperative recurrence. The recurrence of postoperative infection can be prevented by intravenous antibiotic therapy for 6 weeks post-surgery.